(untitled) (Huellas, 2024)
Carrying out land use statistics through remote sensors and Geographic Information Systems (GIS) allows obtaining not only numerical information but also thematic mapping of land uses. It is an important element for the analysis of territorial dynamics, allowing for interpretations to be made about the functioning and structure of the space to be analyzed, which results in very useful information for researchers or decision makers in general. This article presents the results of the analysis of the mapping of peri-urban land uses obtained by remote sensing in the period 1990-2023, for four neighborhoods in the city of Santa Rosa, La Pampa. The dynamics of the main land uses of the study area are analyzed, through the quantification and spatial distribution of eight identified categories: continuous and discontinuous urban; in the process of urbanization or vacant; industrial, commercial and other non-residential uses; urban equipment; horticultural crops and water. For the study and evolution of spatial distribution patterns of these categories, a cartographic overlay methodology is proposed by using GIS tools.